Relationship Quality and Flexibility of Partnering with Suppliers on the Performance of Innovations Mediated by Knowledge Sharing (Case Study on the Steel Industry in Indonesia) - Giovani Anward; Eka Pria Anas (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
Given that most of the operational costs of steel companies are in the main raw materials, steel companies need to pay attention to how they relate to suppliers to improve innovation performance. Thus, this study aims to determine whether the relationship quality and flexibility of partnering with suppliers can affect innovation performance, namely the quality and innovation speed through knowledge sharing. Data was collected through a questionnaire obtained from the national steel company association IISIA and obtained 107 company respondents. The data were processed and analyzed using structural equation modeling (SEM) to test the overall fit of the model and test the causality relationship between variables. The results of this study indicate that the relationship quality has a significant effect on the innovation quality only through knowledge sharing. On the other hand, the quality of the relationship can increase the innovation speed directly without sharing knowledge. The next result is that partner flexibility can increase the innovation speed significantly and also the innovation quality without knowledge sharing. Several managerial implications and suggestions for further research are also presented in this study.